A Secure and Effective Anonymous Integrity Checking Protocol for Data Storage in Multicloud. (27th April 2015) - Song, Lingwei; Zhao, Dawei; Chen, Xuebing; Cao, Chenlei; Niu, Xinxin
Abstract : How to verify the integrity of outsourced data is an important problem in cloud storage. Most of previous work focuses on three aspects, which are providing data dynamics, public verifiability, and privacy against verifiers with the help of a third party auditor. In this paper, we propose an identity-based data storage and integrity verification protocol on untrusted cloud. And the proposed protocol can guarantee fair results without any third verifying auditor. The theoretical analysis and simulation results show that our protocols are secure and efficient.